The Problem of Wellbeing Within the Framework of Quality Management - Kvesko S. B. Svetlana; Kornienko A. A. Alla Alexandrovna; Chaplinskaya Ya. I. Yana Igorevna; Nikitina Yu. A. Yulia Anatolyevna; Chigulina E. (2017, 2017)
Title screen